Non-Invasive Measurement of Humidity Distribution in Polymer Electrolyte Fuel Cells (PEFCs): Part I. In Situ Proof of Concept. Issue 7 (1st July 2022) - Schuller, A.; Schmidt, T. J.; Eller, J.
Abstract : A non-invasive method to determine the local relative humidity (RH) and local high frequency resistance (HFR) distribution from inlet to outlet of polymer electrolyte fuel cells (PEFCs) is presented. The method uses a plurality of electrodes attached to the outer flow field surface to inject alternating currents and measure the resulting voltage amplitudes at the flow fields' surface. Since the measured voltage amplitudes, are highly dependent on the actual electrode positioning on the flow field boundaries, they are interpreted by interpolation between reference measurements at homogeneous relative humidity conditions and known overall cell impedance. The method is implemented experimentally using alternating current injections at a frequency of 1 kHz at well-defined asymmetric in situ N2 /N2 conditions on a 200-cm 2 cell in a 6-cell short-stack. The comparison between the RH distribution and the outlet RH sensor data yields a very good match. The same can be said when comparing the HFR distribution and the global cell HFR. Finally, the sensitivity of the method is tested by varying the mass flow rate with asymmetrical RH conditions. The results are highly reproducible in all the tested conditions.